TO ESTABLISH INTELLECTUAL PSYCHOLOGICAL IMMUNITY OF MAJOR DEPRESSIVE DISORDER PATIENTS BY ANICCATA AND MODERATE POSTMODERN PHILOSOPHY - Sathapong, Kanyawee (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to 1) study establishing intellectual psychological immunity of major depressive disorder patients according to Buddhist philosophy by aniccata 2) study establishing intellectual psychological immunity of major depressive disorder patients by the concept of moderate postmodern philosophy 3) study establishing intellectual psychological immunity of major depressive disorder patients by integration aniccata and the concept of moderate postmodern philosophy. This research is a qualitative one based documentary research upon the analytic, appreciative and applicative approach which leads to the creativity of new body of knowledge in philosophy and religion. The results of research are found as follows: the solving problem of the lack of quality in life of major depressive disorder patients is to establish intellectual psychological immunity by understanding aniccata which is impermanence in everything which serves as a basis to understand suffering and see the soulless (the three characteristics of existence) which help to understand the Four Noble Truths to know suffering, then know the causes of suffering that is caused by the overly adherence of the ego by relieve the adherence according to the means to end suffering of the Noble Eightfold Path which is the noble way that leads to success life that develop human beings with precept, concentration and wisdom with virtue. Because of the solving problem can’t use only one concept, that is the reason to apply the postmodern philosophy to accept the variety of knowledge-based sciences to solve the holistic problem by medical science which treat body disease and mentally disease treatment with the teachings of Buddhism that establish intellectual psychological immunity of major depressive disorder patients. It helps major depressive disorder patients come back to be streghtened and have a peaceful life.